(untitled) - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Saving is not always in the form of cash in the bank; it can also be in the form of commodities (cloves) that are stored at home. The practice of household saving in Negeri Ullath is motivated by socio-cultural factors. Storing cloves as savings has been going on for a long time. This study aims to explore and analyse the motives behind the actions and decisions of saving in the form of commodities by farmer households, and the implications of this form of saving on the social status of local communities and the sustainability of livelihoods. This study uses qualitative methods to obtain field data by conducting in-depth interviews with the informants. The results show that the motive for storing cloves is to meet priority household needs, namely children's education and other needs such as health and social costs, financial independence and prestige. This strategy is based on liquidity considerations and to control spending habits. This finding impacts social ownership and becomes a form of informal insurance